WTO moratorium on customs duties on electronic transmissions: How much tariff revenue have developing countries lost? - Rashmi Banga (South Centre, 2022)
This research paper highlights the adverse impacts of the continuing WTO moratorium on customs duties on electronic transmissions on the developing and least developed countries. The rapidly progressing digitalization along with the ongoing pandemic and the food crisis are creating multiple demands on the government revenues. However, because of the moratorium almost all developing, and least developed countries are losing tariff revenues especially at the time when they are most needed. Not only are they losing the fiscal space but are also losing their regulatory space as they are unable to regulate the growing imports of digitizable products, especially of luxury items like the movies, music and video games. It is estimated that in the period 2017-2020, developing countries and LDCs lost 56 billion of tariff revenue, of which 48 billion were lost by the developing countries and 8 billion by the least developed countries. It is interesting to note that this loss of tariff revenue is from the imports of just 49 products (at HS six-digit). With no clarity on the definition of electronic transmissions (ET) and thereby on the scope of the moratorium, the continuation of the WTO moratorium on customs duties on ET can lead to substantive tariff revenue losses for developing and least developed countries in the future.
Keywords: 300; 3D Printing; COVID-19; Digital Economy; Digital Industrialization; Digitalization; Digitizable Products; Electronic Transmissions; GATS; Least Developed Countries (LDCs); MC12; Pandemic; Tariffs; World Trade Organization (WTO); WTO Moratorium on Customs Duties On Electronic Transmissions